2016
DOI: 10.20960/nh.314
|View full text |Cite
|
Sign up to set email alerts
|

Urinary hydration biomarkers and dietary intake in children

Abstract: Introduction: The importance of hydration is undoubtable but reliable data on hydration status and its relation with diet is lacking. Objectives: We aimed to evaluate the hydration status and its relation to beverages and food intake in children. Methods: A sample of 172 (50% male), 7-11 year-old children was included in this survey. Participants completed a 24 h urine collection; a 24 hours food recall corresponding to the day of urine collection was applied, weight and height were measured and parents/caregi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 15 publications
9
19
2
Order By: Relevance
“…19,29 It provides additional support to studies by other investigators that showed that poor hydration status is common among college students. 19,30,31 Inadequate water intake was significantly associated with the highest Odds (OR=6.4, CI 2.121-19.385) for dehydration among participants.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…19,29 It provides additional support to studies by other investigators that showed that poor hydration status is common among college students. 19,30,31 Inadequate water intake was significantly associated with the highest Odds (OR=6.4, CI 2.121-19.385) for dehydration among participants.…”
Section: Discussionsupporting
confidence: 65%
“…19,29 It provides additional support to studies by other investigators that showed that poor hydration status is common among college students. 19,30,31 Inadequate water intake was significantly associated with the highest Odds (OR=6.4, CI 2.121-19.385) for dehydration among participants. This was found in more than half (59.1%) of all dehydrated participants, further confirming the assertion that most children and adults, and in particular school aged children, adolescences and adults do not consume enough water for their age groups as defined by IOM and EFSA.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations